Indonesia's Role In The Russian And Ukrainian Armed Conflict Peace Process - Adityo Santoso; Eri Radityawara Hidayat; Agus Adriyanto; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The armed conflict between Russia and Ukraine, which began on February 24, 2022, has had a major impact on humanity, geopolitics, security, and world trade. Indonesia is a sovereign country that wants to create peace in the world, so Indonesia should take an active role in pursuing the peace process between Russia and Ukraine. At present, Indonesia has made various efforts, including through President Joko Widodo's official statement against the occurrence of war, participating in issuing resolutions at the UN General Assembly, and also President Joko Widodo's visit to Ukraine and Russia in order to bridge the dialogue process between the two countries. So far, significant results have not been seen from the efforts made by Indonesia and other countries in the world, and the war continues to rage, claiming many lives. However, Indonesia's efforts will continue to influence the process of peace between Russia and Ukraine, as well as show the world that Indonesia is a large country that does not take sides and is deeply concerned about the human tragedy that has occurred. This study uses a qualitative research method. The presentation of data is carried out descriptively based on a comprehensive literature study from books, journals, and news to examine an event that has occurred objectively using an existing theoretical approach.  is written briefly and factually, covering research objectives, research methods, results and conclusions.